Carbohydrate status of sucrose-fed broccoli head during storage and the activity and gene expression of sucrose synthase - Baclayon, Dewoowoogen P.; Matsui, Toshiyuki (Annals of Tropical Research, 2009)
Quality deterioration in broccoli is associated with rapid loss of sucrose after harvest. Hence, this study was conducted to investigate the influence of exogenous application of 10% (w/v) sucrose to broccoli heads during storage at 20⁰C on the activity and gene expression of sucrose synthase. The level of sucrose in the branchlets and florets tissues was improved only within a day and 2 days, respectively, from treatment. The enzyme activity in both portions was inconsistent with SS gene expression thereafter. The decline in sucrose could be a consequence of concerted actions of other harvest related genes in addition to SS. It is possible that SS could be encoded by multi-genes as exhibited in other plant species. Further characterization or isolation of different SS isoforms and their expressions during postharvest senescence would be helpful in the regulation of sugar metabolism in harvested heads during storage.